PENGARUH PERDAGANGAN INTERNASIONAL, PERDAGANGAN JASA, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI KAWASAN NEGARA ASEAN PERIODE 2018-2022 DALAM PERSPEKTIF EKONOMI ISLAM - Chandra Okspendri; Yulistia Devi (Program Studi Ekonomi Syariah, 2024)
Economic growth is the most important part of economic policy in any country or economic system. Based on data from the ASEAN Statistics economic growth has fluctuated from year to year. Factors that affect a country's economic growth are export activities and inflation. Based on the phenomena that occur, the study aims to find out the relationship of International Trade, Trade in Services and Inflation to economic growth in ASEAN and in the view of Islamic Economics.This research uses quantitative research with an associative nature. The data source used is secondary data published by the official ASEAN statistics webside and supporting data from other official webside. The statistical tool used for data analysis uses e-Views 10 software.The results of this study indicate that partially, the International Trade variable has no effect on Economic Growth, then the Service Trade variable has no effect on Economic Growth and the Inflation variable has a significant effect on Economic Growth. The simultaneous test results show that International Trade, Trade in Services and Inflation together have no significant effect on Economic Growth in the ASEAN Region in 2018-2022.